2015
DOI: 10.1080/10810730.2015.1018625
|View full text |Cite
|
Sign up to set email alerts
|

Persuasive Effects of Linguistic Agency Assignments and Point of View in Narrative Health Messages About Colon Cancer

Abstract: The authors explored the effects of linguistic agency and point of view on narrative force. Participants (N = 499) were randomly assigned to read one version of an article about colon cancer, defined by a 2 (disease agency: cancer, human) × 2 (temporal agency: death, human) × 2 (point of view: first person, third person) between-subjects design. Disease agency language assigned agency to cancer (e.g., "Cancer developed in me") or to humans (e.g., "I developed cancer"). Temporal agency language described death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 26 publications
0
17
0
7
Order By: Relevance
“…Response efficacy. The expectations of efficacy of the preventive response (quitting smoking) were measured using a scale [ 25 ] comprising five items (e.g., “a life without tobacco reduces the risk of health problems”; from 1 = strongly disagree to 7 = strongly agree; α = 0.85, M = 5.91, SD = 0.97) (see Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Response efficacy. The expectations of efficacy of the preventive response (quitting smoking) were measured using a scale [ 25 ] comprising five items (e.g., “a life without tobacco reduces the risk of health problems”; from 1 = strongly disagree to 7 = strongly agree; α = 0.85, M = 5.91, SD = 0.97) (see Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has found that people better imagine the thought processes of protagonists (e.g., “Did you see what the main character was thinking and seeing?”) when narrative messages are written in the first compared with the third person [ 24 ]. Therefore, it has been proposed that first-person narratives make it easier for the audience to identify with the protagonist [ 16 , 20 , 25 ]. In this context, identification with the protagonist (or the capacity to feel and adopt the point of view of the protagonist of the narrative; [ 14 , 26 , 27 ] is proposed as a primary mediator .…”
Section: Introductionmentioning
confidence: 99%
“…En la narración en tercera persona el personaje era presentado por su nombre por el narrador de la historia: "Miguel tiene 35 años y empezó a fumar a los 15". Este procedimiento experimental para manipular la voz narrativa ha sido empleado con éxito en un gran número de investigaciones (Banerjee y Greene, 2012;Chen et al, 2017;Chen, McGlone y Bell, 2015;Nan et al, 2015;Nan et al, 2017).…”
Section: Narración Y Manipulaciones Experimentalesunclassified
“…La auto-eficacia se define como la confianza que una persona tiene en su capacidad de realizar y mantener un cierto comportamiento en una situación dada (en este caso, abstenerse de fumar cuando se ha abandonado dicho hábito) (Spek, Lemmens, Chatrou, Kempen, Pouwer y Pop, 2013). Para medir las expectativas de auto-eficacia se utilizó una escala compuesta por 6 ítems, elaborada a partir de Chen et al (2015), McQueen, Waters, Kaphingst, Caburnay, Sanders Thompson, Boyum y Kreuter (2016), Spek et al, (2013) y Williams et al (2011): "creo que tengo capacidad para dejar de fumar cuando me lo proponga", "estoy seguro de que puedo dejar de fumar", "sé lo que debería hacer para dejar de fumar", "si dejara de fumar y alguien me ofreciera un cigarrillo sabría resistirme y no fumaría", "si dejara de fumar y acudiera a una fiesta con amigos o con familiares, sabría cómo actuar para no fumar", "si ya he decidido no volver a fumar estoy seguro de que no cogería un cigarrillo aunque me sintiera triste o ansioso" (desde 1 = muy en desacuerdo, hasta 7 = muy de acuerdo). Se construyó un índice de expectativas de auto-eficacia a partir de calcular el promedio en los seis ítems (α = .88).…”
Section: Variables Dependientesunclassified
See 1 more Smart Citation